Last of the breed : live in concert [videorecording (DVD)] - Nelson, Willie, 1933-; Price, Ray, 1926-2013; Haggard, Merle (Top Hat Tunes, 2023)
Willie Nelson, Merle Haggard, Ray Price are the last of their breed, elder statesmen of classic country music who have inspired artists for decades.